Comprehensive Health Surveillance of Radiation Workers in Nuclear Medicine: Evaluation of Hematological, Hormonal, Biochemical, and Dosimetric Profiles at NINMAS - Mia, Md Shohag; Mehdi, Hasan; Biswasarma, Sanchoy Chandra; Siddiquee, Md Nur E Alam; Islam, Sanjida; Kadir, Muhtasim; Uddin, Md Jashim; Hossain, Md Nahid (Bangladesh Journal of Medical Physics, 2025)
Radiation workers in a clinical setting generally are engaged with ionizing radiation like x-ray, gamma ray, which can be harmful due to its potential biological damage. Locally relevant surveillance data are limited in Bangladesh. So, a systematic health checkup is required to early detect the biological adverse effects. The purpose of the study is to assess hematological, hormonal, biochemical, and dosimetry data among radiation workers working in nuclear medicine facilities at the National Institute of Nuclear Medicine & Allied Sciences (NINMAS). A group of radiation workers involved with the scintigraphy section underwent this cross-sectional study. To carry out this study, Complete Blood Test (CBC), urine R/E, thyroid function tests (TSH, FT4) of the radiation workers were done, and thermoluminescent dosimeter (TLD)-based personal dose reports were measured quarterly. Occupational doses of the radiation workers were correlated with all the biological reports, which were assessed against standard clinical ranges. Radiation dose received by the participants was lower than 0.05 mSv, which is well below the occupational dose limit of 20 mSv per year according to the ICRP 103. Different parameters for Hematology were mostly shown within normal limits, where the variation of lymphocyte values was found with minor change, with one female case of anemia (Hb: 8.3 g/dL). Thyroid hormonal values were within reference ranges, and the TSH value of two female workers showed upper borderline, with one female case of elevated FT4. In a few cases, trace glycosuria and pyuria were found in urinalysis. Effective radiation-protection techniques were consistent with measured doses that were significantly below ICRP limits. The importance of regular surveillance and clinical follow-up is highlighted by the anomalies that have been detected, such as anemia and thyroid dysfunction. The small, uncontrolled sample makes the results illustrative; larger, long-term investigations with more biomarkers are necessary. Ban. J. Med. Phys., Vol -16, Issue -2, 2025 : 84-89